2023
DOI: 10.1186/s12967-023-03998-8
|View full text |Cite
|
Sign up to set email alerts
|

Integrated multi-omics analyses and functional validation reveal TTK as a novel EMT activator for endometrial cancer

Abstract: Background Cancer-testis antigens (CTAs) are often expressed in tumor and testicular tissues but not in other normal tissues. To date, there has been no comprehensive study of the expression and clinical significance of CTA genes associated with endometrial cancer (EC) development. Additionally, the clinical relevance, biological role, and molecular mechanisms of the CTA gene TTK protein kinase (TTK) in EC are yet to be fully understood. Methods Us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 65 publications
(85 reference statements)
0
2
0
Order By: Relevance
“…2J–L ). Furthermore, we explored whether TTK regulates the expression of ANXA2 through AZ3146, a specific inhibitor of TTK [ 32 ]. We obtained the IC50 values of the ECA109 and KYSE30 cell lines by CCK8, which were 30.27 μmol/L and 23.88 μmol/L respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2J–L ). Furthermore, we explored whether TTK regulates the expression of ANXA2 through AZ3146, a specific inhibitor of TTK [ 32 ]. We obtained the IC50 values of the ECA109 and KYSE30 cell lines by CCK8, which were 30.27 μmol/L and 23.88 μmol/L respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study carried out by Albogami, in which The Human Protein Atlas database was accessed to evaluate the protein and gene expression levels of threonine tyrosine kinase (TTK) in different samples, negative regulation of threonine tyrosine kinase (TTK) was observed at both the transcriptional and protein levels in non-cancerous tissues adjacent, but high levels were detected in tumor samples (Albogami, 2022). Additionally, other studies have also demonstrated that threonine tyrosine kinase (TTK) is highly expressed in neoplastic tissues when compared to adjacent healthy or benign tissue, such as in endometrial and bladder cancer (F. Chen et al, 2018;Miao et al, 2023). Regarding epigenetic mechanisms, we investigated whether methylation could be a gene regulation pathway for threonine tyrosine kinase (TTK).…”
Section: Discussionmentioning
confidence: 99%